A criança e as relações parentais no contexto da separação conjugal: um estudo de caso - Fritsch, Caroline de Abreu Prola (2016)
This present study aimed to investigate the comprehension and the fantasies of children related to the marital separation from their parents, contextualizing them with the established parental relationship. Therefore, a qualitative exploratory study was taken, the research was done by a study of multiple cases with three families having children of six years old, and whose parents have been divorced for not longer than two years, at the moment of this research. In order to collect the data with the children, the following projective tests were used: Fables Test – pictorial version and the procedure of Family Cartoons with Stories. The parents were individually interviewed for a Sociodemographic Data Interview and Interview about Marital Separation and Children. The main reference while examining the data was the content analysis. Based on the data received, it was possible to perceive differences on the perception of the children towards the meaning that parental relationships took on the postdivorce context. Two participants stated that parents were destined a position characterized by affection, whilst three of them said the mother had a conflictive position. In such way, on this study, on the eyes of the child the mother figure was understood by the children as source of safety, replacing the care. Related to the fantasies of the children on their parents post-divorce scenario, the fantasy of aggression dislocated to the environment prevailed and the fantasy of family aggression as well. There could be also pointed the fantasies of abandonment and death, showing the impact of the children in relation to the marital separation. It could be comprehended that the possible consequences for the children who had its parents separated are shown through emotional disorder, yet, the quality of the affection among the parents figure and the children acts as a mediator when great changes are faced, in the case of a separation, characterizing the emotional disorder of the children as temporary or expected to the moment of crisis the family experienced. In this way, it is emphasized the need of listening to the children on the marital separation process, enabling a space for distress, doubts and fantasies to be freely expressed. Even though there is connection, affection, and concern from the parents the marital separation occurrence can make the children feel fear and anxiety, since they are found in a situation passive over happenings prior to the decision of separation.